SCALE APPROACH TO URBAN STUDIES WITH GIS-TOOLS - Kostrikov, Sergiy (Human Geography Journal, 2014)
This paper represents the well-known scale approach in urban studies upon a new perspective. This perspective to involve through GIS-tools in relevant research not only traditional integer-valued scale measurements and modelling, but also fractal ones reveals the unique level of details in urban system analysis. The paper explains while the scale approach became drastically crucial for contemporary human geographers – because of newly technological advances. Few key basics of urban studies with the scale approach through GIS-tools have been introduced. The survey detailed enough due to applying fractal dimensions in the urban spatial structure analysis with the original GIS software has been provided. Some case studies and examples of the software GUI with the scale approach implemented have been introduced.